KEBIJAKAN HUKUM PIDANA PENGGUNAAN NARKOTIKA GOLONGAN 1 (SATU) JENIS “GANJA” UNTUK KESEHATAN - Karen Abigael Pangkey; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2019)
Health is a healthy condition, physically, mentally, spiritually, and socially that enables everyone to live productively socially and economically. In maintaining his health, in order to survive, it is not uncommon for a person to use narcotics as a treatment he must live. Like the incident in the 111 / Pid.Sus / 2017 / Pn.Sag case. Where Yeni was given Marijuana by her husband as a treatment, previously Yeni had tried various treatments in the medical and traditional fields. When there was a urine test in Fidelis's office, Fidelis asked the National Narcotics Agency about how to treat cannabis treatment, a few days after that, Fidelis was immediately arrested at his home and detained. While in prison, Yeni passed away. How is the application of the principle of justice in imposing crimes against Fidelis? Fidelis was sentenced to 8 (eight) months in prison and a fine of Rp1,000,000,000 (one billion rupiah) and was replaced with a prison of 1 (one) month if he could not pay the fine. In this study, the author uses normative legal methods and uses interview data as supporting data. The results of the study that the authors conclude that Fidelis should not be convicted because Fidelis is an act of force or in an emergency, here there is freedom of judges in deciding cases, and there is a difference between applicable law (das sollen) with existing practice (das sein).